Challenges of Climate Change Adaptation in Brazilian Municipalities: A Systematic Literature Review - Lopes, Adriano Felipe Oliveira; Rodrigues, Edna Aparecida Nico (National Journal of City Management, 2025)
Objective – To identify the challenges faced by Brazilian municipalities in the implementation of climate adaptation actions.Methodology – Systematic review of 77 articles (2014–2024) from the databases ScienceDirect, Scopus and Web of Science.Originality/relevance – Fills a gap regarding the implementation of municipal climate adaptation policies in Brazil.Results – Among the 77 articles analysed, involving 309 researchers, case studies (39%) and quantitative methods prevail, with a focus on São Paulo and Rio de Janeiro, highlighting challenges in integrating urban and climate policies.Theoretical/methodological contributions – Reveals scientific fragmentation and regional concentration of research.Social and environmental contributions – Demonstrates a disconnect between public policies and local demands. Indicates weaknesses in municipal climate governance and the need to overcome regional technical and financial inequalities.
Keywords: Climate change; Climate governance; Urban resilience